Raeis Jomhur Mir Qanbar . President Mir Qanbar - Shirvani, Mohamad (Iran, 2005)
A 75 year old man with a megaphone pedals into town flying a red flag with a quote from the Qur’an: ‘a big victory supported by God is imminent.’ Mir Qanbar, a retired civil servant from remote Azerbaijan in Iran, is running for President of the Islamic Republic. It’s not his first campaign: he’s run five times for Congress and in three previous attempts to capture the Presidency he’s been disqualified each time. His organisation consists solely of his disabled friend Seifollah, who distributes leaflets from a mule-drawn cart and who has been promised the role of Minister for Health in a Qanbar regime. It’s more Don Quixote than Screaming Lord Sutch since Qanbar is still confident that he has a real chance. Now, will the documentary crew help him secure a meeting with President Khatami and prevent the authorities from rejecting his candidacy yet again?